Corporate Diversification, Economies of Scope, and the Risk–Return Relationship - Sakhartov, Arkadiy V. (Academy of Management Review, 2024)
The negative relationship between corporate risk and corporate returns, also known as the “Bowman paradox,” has been an important puzzle in strategy research that has motivated dozens of empirical studies. Theoretically, the paradox was explained with an appeal to contingent managerial preferences for risk or to heterogeneous managerial capabilities. A popular alternative view has been that the paradox is merely an empirical artifact and, thus, does not need to be explained with management theories. Furthermore, the view that the negative risk-return relationship does not need to be explained theoretically translated into a bottom line for nearly five decades of research on diversified firms—that the paradox cannot be explained theoretically based on the context of corporate diversification. This study counters that pessimistic view and develops a formal model to explain theoretically how the negative risk-return relationship exists in diversified firms due to the interplay of two types of economies of scope. Thus, the Bowman paradox is explained in this study parsimoniously, with the fundamental features of the context of corporate diversification that exist regardless of the variation in managerial preferences for risk or in managerial capabilities.